2017
DOI: 10.3892/mmr.2017.8161
|View full text |Cite
|
Sign up to set email alerts
|

Interference of Notch 1 inhibits the proliferation and invasion of breast cancer cells: Involvement of the β‑catenin signaling pathway

Abstract: Breast cancer is one of the most common types of carcinoma in humans. The aim of the present study was to identify the role of Notch 1 in the proliferation and invasion of human breast cancer cells. Firstly, the levels of Notch 1 were determined by western blot analysis in breast cancer cell lines, and the results revealed that the expression levels of Notch 1 were markedly higher in MDA‑MB‑231 and MCF‑7 cells, and lower in MCF‑10A cells, compared with human mammary epithelial cells. An MTT assay was used to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 26 publications
1
14
0
1
Order By: Relevance
“…The role of the Notch pathway in cancers has been determined according to the effect of Notch pathway on cell proliferation, migration, and invasion [22][23][24][25][26]. In the present study, we demonstrated that TRIM67 overexpression can upregulate Notch1, Jagged1, and NICD.…”
Section: Discussionsupporting
confidence: 58%
“…The role of the Notch pathway in cancers has been determined according to the effect of Notch pathway on cell proliferation, migration, and invasion [22][23][24][25][26]. In the present study, we demonstrated that TRIM67 overexpression can upregulate Notch1, Jagged1, and NICD.…”
Section: Discussionsupporting
confidence: 58%
“…While most factors downstream of Notch increase the proliferative rate of the cell, Hes1 downregulates E2F1 expression which inhibits cell cycle progression (Hartman et al, 2009;Strom et al, 2009). Notch also activates key oncogenic signalling pathways with pleiotropic effects on cellular function including proliferation, such as c-Myc, Ras and Wnt (Mittal et al, 2009;Aster et al, 2017;Lai et al, 2018). Choy et al, 2017;Kong et al, 2018;Rui et al, 2018;Tu et al, 2019).…”
Section: Cell Proliferationmentioning
confidence: 99%
“…The dysfunction of the Notch1 signaling pathway may lead to abnormal differentiation or undifferentiation, and may eventually lead to the malignant transformation of these cells. Of note, it has been revealed that changes in Notch1 signaling are associated with a number of human cancers (26)(27)(28); however, the role of Notch1 in osteosarcoma has yet not been elucidated. HES1 is a highly conserved basic helix-loop-helix transcription inhibitor, which mediates its biological effects by binding to N-cassettes (CACNAG) in the entire genome and recruiting chromatin modification factors to these sites (29,30).…”
Section: Discussionmentioning
confidence: 99%